Water Use Efficiency in Vertical Cropping System with Volcanic Ash Media by Using Biochar and Urban Waste Compost Fertilizer as Soil Amendement - Mulyono Nitisapto; Azwar Maas; Benito Heru Purwanto; Putu Sudira (Jurnal Ilmu Pertanian, 2019)
Applying volcanic ash as planting media has to cope with several constrains: it quickly became sediment and hardened when exposed to water. One of the efforts to improve its physical condition is by utilizing biochar, which is one of amendment materials that can improve the soil quality. This study used vertical column container made from PVC to enable vertical plant arrangement. Volcanic ash requires additional nutrient intake from organic fertilizer such as urban waste compost. The objective of this study was to identify the proper dose combination of volcanic ash, biochar, urban waste compost fertilizer and column population per m2 to sustain the growth of curly lettuce in vertical cropping system, as well as the water use efficiency. This study was designed by using the Completely Randomized Design (CRD) Factorial with three factors. The first, second and third factors consisted of Biochar M1, M2 and M3 (25; 33; and 50 %), compost fertilizer doses of K1, K2, and K3 (25; 33; and 50 %), and column density of P1, P2 and P3 (4 columns/m2, 3 columns/m2 and 2 columns/m2), respectively. The total combination was 3 x 3 x 3 and each was repeated 3 times. Resulted data of this study consisted of growth and crops and analyzed by using the Analysis of Variance and continued with the HSD Tukey 5% Test (Honest significant deference). The water use efficiency (g/kg) can be formulated as the production of dry material per total water during the cultivation season (g/kg). Results of this study showed the highest fresh consumption result was obtained from treatment M3K3 in 556 g/column (comparison of volcanic ash, charcoal husk and compost = 25 : 25 : 50 %) and the best water-use efficiency was 2.30 g/kg.